Sosialisasi Edukasi Pencegahan Risiko Jatuh Lansia di Panti Jompo Sidoarjo - Etik Lusiani; Arief Widya Prasetya; Agung Kurniawan (Universitas Baiturrahim, 2026)
Organ dysfunction in the elderly, including musculoskeletal dysfunction, causes a decrease in joint flexibility and mobility, which can affect the balance of the elderly, putting them at risk of falling. Based on a survey conducted at the Sidoarjo Nursing Home, there were 5 elderly people who were at moderate risk of falling and 3 who were at high risk. The purpose of the educational outreach was to increase knowledge about fall prevention, the causes and consequences of falls, and to provide balance training. The process began when caregivers at the Sidoarjo Nursing Home submitted a request to provide health information to the LPPM STIKES Katolik St Vincentius a Paulo unit, which was then approved, and community service activities were carried out. There were 26 respondents for the health education activity, which was carried out in the following stages: respondents were given a questionnaire before the education, the material was presented, respondents were given the opportunity to ask questions about the material on fall risk in the elderly and balance exercises, and then respondents were given a questionnaire after the education. The results after the health education process showed a change in the level of knowledge. Before the activity, 19 respondents (73%) had insufficient knowledge, 5 respondents (19%) had adequate knowledge, and 2 respondents (8%) had good knowledge about fall risk prevention. After receiving health education, 13 respondents (50%) had good knowledge, 8 respondents (31%) had adequate knowledge, and 5 respondents (19%) had poor knowledge about preventing falls in the elderly. Based on the results of this community service activity, we recommend that the Sidoarjo Nursing Home implement balance training for the elderly by providing assistance to help them maintain and preserve their balance to prevent the risk of falling.